Church Planting in Niger: A Proposal for Integrating Wesleyan Theology with Church Planting Movements - Wright, David (My University, 2013)
Despite over eight years of Christian witness, the West African country of Niger is still considered unreached by Christian missiologists. In the face of ongoing ministry challenges in Niger a new perspective is appropriate. Recent trends in missions recommend Church Planting Movements as a model for church-planting ministry in cross-cultural contexts. The church planting movements model may offer some solutions for church planting in Niger but the model tends to suffer from faulty prooftexting and inadequate theology related to the church and mission. Using theological reflection as a guiding model, church-planting-movement theology and practices are compared to John's Wesley's theology and practice. As a practical theologian, Wesley provides an example of how theological reflection can be more adequately integrated into the practice of mission. Through theological reflection and consideration for the Nigerien context, this thesis develops a church-planting ministry plan for the Free Methodist Church in Niger.
Keywords: Niger, Church planting, theology, Wesleyan